PENGARUH PENDAPATAN DAN PERUBAHAN PERILAKU PEMILIK LAHAN TERHADAP ALIH FUNGSI LAHAN KARET MENJADI KELAPA SAWIT (STUDI KASUS: NAGARI SUNGAI DAREH KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA) - Suci Ramadani; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research was to determine the effect of income and changes in behavior of landowners on the conversion of rubber plantation land to oil palm in Nagari Sungai Dareh. This research can be used as a reference for farmers before carrying out land conversion. Data analysis methods used include Validity, Reliability, Classical Assumptions (Normality, Autocorrelation, Multicollinearity, Heteroscedasticity), Multiple Linear Regression Tests, Hypothesis Tests (T Test, F Test), and Test the Coefficient of Determination R2. The results of this study indicate that the regression coefficient has a value of 0.391 (X1) and 0.276 (X2) if every increase of 1 unit of income variable and changes in the behavior of landowners, it will affect land conversion by 0.391 (X1) and 0.276 (X2). Then, the t count (X1) is approximately equal to 2.811 and is greater than t table which is 1.999 (2.811>1.999), and the sign is close to 0.007 to 0.05. This indicates that H1 is rewritten or H0 is collapsed. Then the calculated t value (X2) is approximately equal to 2.967, which is larger than the t table, which is approximately 1.999 (2.967 > 1.999), and a sig of approximately 0.004 to 0.05. This indicates that H1 is rewritten or H0 is collapsed. There is a yield from the R2 experiment of about 0.209, or 20%. It is believed that most of the independent variables can explain the dependent variable with an accuracy of 20.9%, while other independent variables can explain the remaining 80%. Based on significant changes partially on the t test X1 and X2 on land conversion in Nagari Sungai Dareh.